The Influence of Islamic Religious Education Learning on the Character Formation of Students in Schools - Andi Suhendra Siregar (AT-TAKILLAH : Jurnal Pendidikan dan Keislaman, 2025)
This study aims to analyze the influence of Islamic Religious Education learning on the character formation of students in schools. Character education has become an important issue in the educational field due to the increasing moral challenges faced by students in the modern era. Islamic Religious Education is expected to contribute significantly to developing positive attitudes and behaviors such as honesty, discipline, responsibility, respect, and social care among students. This research employed a quantitative approach using a survey research design. The population of this study consisted of students at the selected school, while the sample was determined using purposive sampling techniques. Data were collected through questionnaires, observations, and documentation. The questionnaire used a Likert scale to measure students’ perceptions regarding Islamic Religious Education learning and character formation. The collected data were analyzed using descriptive statistics and simple linear regression analysis. The findings revealed that Islamic Religious Education learning has a positive and significant influence on students’ character formation. Students who actively participated in religious learning activities demonstrated better discipline, honesty, responsibility, and social behavior. Teachers, school environment, and religious activities also played important roles in supporting character education. However, several challenges such as low student motivation and limited learning innovation were still found during the implementation process. Therefore, schools are encouraged to improve the quality of Islamic Religious Education learning through interactive teaching methods, technology integration, and collaboration between teachers and parents. Overall, this study concludes that Islamic Religious Education learning contributes significantly to developing students with positive character and moral values in schools.